California State College at Hayward Catalog 1967-1968 - California State College, Hayward:::::: (1967)
A catalog of courses offered by California State College at Hayward for the academic year 1967-1968. Includes academic calendar, history of the college, names of faculty and administrators, and descriptions of courses and degrees offered.